Comparison of nutritional status of university students of two Asian countries - Khattak, Muhammad Muzaffar Ali Khan; Draman, Samsul; Khan, Alam; Khattak, M. Usman (Emerald Group Publishing Limited Howard House Wagon Lane Bingley BD16 1WA United Kingdom, 2012)
Purpose – The purpose of this paper is to compare energy and macro-nutrients intake in university hostel students in two countries of Asia. Design/methodology/approach – Female students from the hostels of International Islamic University, Malaysia (IIUM), Kuantan Campus and NWFP, Agricultural University Peshawar, Pakistan were assessed for energy and macro-nutrients intake. A total of 140 students were registered who volunteered to participate in this study. The age range of the registered students was 22-26 years. On the day of the registration, age, height and weight were recorded; also, food frequency questionnaires (FFQs) were provided. The participants were asked to record alternately for three days whatever they ate during the prescribed week. Out of 140 students 139 returned the FFQs. From the anthropometry, the BMI was used to assess the under, ideal, over-weight and obese students. From the FFQs, energy and nutrient intakes were calculated using the food composition tables for Malaysia and Pakistan and compared with the recommended nutrients intakes (RNIs). Findings – The body weight for the required height among the Malaysian students was lower by 7.81 per cent than the reference value, whereas the body weight of Pakistani students matched to the reference weight for height. The Malaysian students were 28.0, 61.0, 5.5 and 0.9 per cent under, ideal, over-weight and obese, respectively, whereas Pakistani students were 100 per cent in the category of ideal-body weight. The total energy consumption was higher among Malaysian students by 9.93 per cent compared to the reference requirements, whereas the Pakistani students claimed to meet the requirements. In terms of nutrients balancing the Malaysian students were having the ideal combination of the macro-nutrients and it was within the recommended range of 55-60, 15-20 and 25-30 per cent for carbohydrates, protein and fat, respectively; whereas the balancing of the macro-nutrients was poor among the Pakistani students and met the energy requirements at the expense of fat consumption. Originality/value – The paper suggests that there is imbalance in macro-nutrients intake among the students.